Management of prolonged meconium evacuation in preterm infants: A survey‐based analysis in German Neonatal Intensive Care Units. (13th September 2022) - Lange, Matthias; Figura, Yannick; Böhne, Carolin; Beske, Florian; Bohnhorst, Bettina; Heep, Axel
Abstract: Aim: Due to the functional immaturity of bowel motility, a delayed passage frequently requires evacuation of meconium in preterm infants. Often rectal enemas and oral laxatives are used to manage these bowel evacuation disorders. Methods: An online survey was sent to all 163 high‐level Neonatal Intensive Care Units (NICUs) in Germany. The participants were queried on rectal enemas, laxative therapy and outcome incidences. Results: A total of 110/163 (67.5%) hospitals participated in the study. 103/110 (93.6%) participating sites applied rectal enemas in cases of delayed meconium evacuation and 63/110 (57.3%) additionally used oral laxatives. In total, 15 different solutions and 7 different application systems were used for rectal instillation. Preterm infants receiving enemas within the first 48 hours after birth were found to have a significantly lower incidence of FIP ( p  = 0.006). Altogether 8 different oral laxatives were utilised. Conclusion: Therapeutic approaches to the management of prolongated meconium evacuation differ widely among German NICUs. Our survey highlights the diversity of applied substances, means of application and differences in duration and frequency of interventions. Macrogol was commonly used in neonates as an oral laxative despite the lack of approval from the manufacturer.